"B Is for Bunny": Contested Sign‐Making and the Possibilities for Performing School Literacy Differently. Issue 1 (8th January 2021) - Kontovourki, Stavroula; Siegel, Marjorie
Abstract: The tremendous interest in multimodality within the field of literacy education has challenged the verbocentric literacy landscape of schools. Research on multimodality in classroom spaces has suggested that combining and juxtaposing multiple sign systems is a generative act of transforming meanings. Yet, attention to entanglements of pedagogy and power has been rare in the research on students' engagement with multimodality. In this article, we complicate the research on the generative potential of children's multimodal sign‐making in school by tracing the ways this process is saturated with power. Using a theoretical mash‐up, performative semiotics, we read a classroom event, situated in a computer lab, in which two kindergartners regarded as successful literacy learners designed digital texts about a bunny that some children reported seeing on a field trip. The multiple meanings of bunny that the children negotiated are theorized as chains of contested sign‐making that are performative. In tracing both sign‐making and performativity, the analysis makes visible the politics of schooled literacy and the way children's performances appear fixed yet are destabilized in their interactions, thus complicating the assumption that multimodality is a generative process that can transform schooled literacy. This analytic mash‐up also focuses attention on the instability of classroom interactions and shows how this provides openings for performing literacy differently even as they remain bound to normalized and naturalized ways of being literate in school. Thus, we argue that claims about multimodality require attention to the way both fixity and instability produces school literacy performances.